Description of Durckheimia lochi n. sp., with an annotated checklist of Australian Pinnotheridae (Crustacea: Decapoda: Brachyura) - Ahyong, Shane T.; Brown, Diane E. (Zootaxa, 2003)
A new species of pinnotherid crab, Durckheimia lochi, is described from the Great Barrier Reef, representing the first Australian record of the genus. The new species differs from its congeners chiefly by the combination of a transverse anterior carapace margin, a deep, slit-like, median frontal carapace notch, a cristate, but interrupted longitudinal median carina on the carapace, and in features of the third maxilliped. Pinnotheropsis yokotai Kubo, 1939, is removed from the synonymy of D. caeca Bürger, 1895, and the generic position of D. besutensis Serène, 1967, is discussed. A key to the species of Durckheimia and an annotated checklist of the known Australian Pinnotheridae are provided. Previous records of Pinnotheres novaezelandiae Filhol, 1885, P. obesus Dana, 1852, and Pinnixia faba (Dana, 1851) from Australia are corrected.